Comparative genomics analysis of endangered wild Egyptian Moringa peregrina (Forssk.) Fiori plastome, with implications for the evolution of Brassicales order - AbdAlla, Heba A. M.; Wanga, Vincent Okelo; Mkala, Elijah Mbandi; Amenu, Sara Getachew; Amar, Mohamed Hamdy; Chen, Lingyun; Wang, Qing-Feng (Frontiers in Genetics, 2023)
Abstract Moringa is a mono-genus belonging to the Moringaceae family, which includes 13 species. Among them, Moringa peregrina is plant species native to the Arabian Peninsula, Southern Sinai in Egypt, and the Horn of Africa, and comprehensive studies on its nutritional, industrial, and medicinal values have been performed. Herein, we sequenced and analyzed the initial complete chloroplast genome of Moringa peregrina. Concurrently, we analyzed the new chloroplast genome along with 25 chloroplast genomes related to species representing eight families in the Brassicales order. The results indicate that the plastome sequence of M. peregrina consists of 131 genes, with an average GC content of 39.23 %. There is a disparity in the IR regions of the 26 species ranging from 25,804 bp to 31,477 bp. Plastome structural variations generated twenty hotspot regions that could be considered prospective DNA barcode locations in the Brassicales order. Tandem repeats and SSR structures are reported as significant evidence of structural variations among the 26 tested specimens. Furthermore, selective pressure analysis was performed to estimate the substitution rate within the Moringaceae family, which revealing that the ndhA and accD genes are under positive selective pressure. The phylogenetic analysis of the Brassicales order produced an accurate monophyletic annotation cluster of the Moringaceae and Capparaceae species, offering unambiguous identification without overlapping groups between M. oleifera and M. peregrina, which are genetically strongly associated. Divergence time estimation suggests that the two Moringa species recently diversified, 0.467Ma. Our ﬁndings highlight the first complete plastome of the Egyptian wild-type of M. peregrina, which can be used for determining plastome phylogenetic relationships and systematic evolution history within studies on the Moringaceae family. Keywords: Comparative genomics, endangered, wild Egyptian Moringa peregrina, plastome, phylogeny, estimation time.